2007
DOI: 10.1086/510565
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Ration Size and Hypoxia on Specific Dynamic Action in the Cod

Abstract: We present the first data on the effect of hypoxia on the specific dynamic action (SDA) in a teleost fish. Juvenile cod (Gadus morhua) were fed meals of 2.5% and 5% of their wet body mass (BM) in normoxia (19.8 kPa Po(2)) and 5% BM in hypoxia (6.3 kPa Po(2)). Reduced O(2) availability depressed the postprandial peaks of oxygen consumption, and to compensate for this, the total SDA duration lasted 212.0+/-20 h in hypoxia, compared with 95.1+/-25 h in normoxia. The percentage of energy associated with the meal d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
99
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(103 citation statements)
references
References 32 publications
4
99
0
Order By: Relevance
“…and averaging values in the lowest mode (SMR swim_hist ) to exclude elevated values resulting from spontaneous activity Korsmeyer et al, 2002;Jordan and Steffensen, 2007;Svendsen et al, 2012). For this third method, a double normal distribution was fitted to a frequency histogram of the raw M O2 data: elevated values of M O2 corresponding to the first normal distribution were excluded and the second normal distribution with lower M O2 values was used to provide an estimate of M O2 at U=0.75BLs…”
Section: Swimming Respirometrymentioning
confidence: 99%
See 2 more Smart Citations
“…and averaging values in the lowest mode (SMR swim_hist ) to exclude elevated values resulting from spontaneous activity Korsmeyer et al, 2002;Jordan and Steffensen, 2007;Svendsen et al, 2012). For this third method, a double normal distribution was fitted to a frequency histogram of the raw M O2 data: elevated values of M O2 corresponding to the first normal distribution were excluded and the second normal distribution with lower M O2 values was used to provide an estimate of M O2 at U=0.75BLs…”
Section: Swimming Respirometrymentioning
confidence: 99%
“…However, because swimming respirometry is impractical for some species (Reidy et al, 1995;Jordan and Steffensen, 2007), chasing followed by air exposure likely provides the best alternative. Furthermore, we found that SMR can accurately be estimated from data obtained using swimming respirometry.…”
Section: Conclusion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found no significant differences in growth and explained that the decrease in food uptake would be an indirect mechanism to save energy in a hypoxic environment, and reduced growth would thus be an indirect effect. Feeding experiments by Jordan and Steffensen (2007) showed that cod, fed under normoxic conditions at a food rate of 2.5 and 5% of body weight, used 40 and 55% of their oxygen uptake for specific dynamic action, respectively, while they used 69% under hypoxic conditions leaving much less oxygen for other metabolic activities. Similar results were found by Bejda et al (1987) for red hake Urophycis chuss, where especially younger stages increased their swimming activity to escape low oxygen waters and all stages reduced food search activities with decreasing oxygen content.…”
Section: Growthmentioning
confidence: 99%
“…The SDA response was calculated empirically for each individual (Jordan and Steffensen, 2007;McKenzie et al, 2013). To correct for effects of handling on metabolic rate, Ṁ O2 values from the sham treatment were subtracted from the true SDA treatment, respirometry cycle by cycle.…”
Section: Experimental Animals and Selection Of Extreme Phenotypesmentioning
confidence: 99%